PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA GURU NON PNS SMKN SE-KABUPATEN SUMBAWA BARAT) - Rahmawati Rahmawati (Master of Management, Mataram University, 2015)
This study aimed to observe the significant influence of Organizational Climate andJob Satisfaction on the Organizational Citizenship Behavior of non-civil teacher in WestSumbawa Regency, either simultaneously or partially, and to determine which dominantvariables that influence theirOrganizational Citizenship Behaviours. The current studybelonged to an associative type of research using saturation sampling technique. The studyinvolved 65 participant whose status were non-civil servant teachers of Vocational HighSchools. The data analysis technique employed was multiple linier regression.Results of the study showed that Organizational Climate and Job Satisfactionsimultaneously had a significant influence on Organizational Citizenship Behavior on thenon-civil servant vocational school teachers in West Sumbawa Regency. The variables ofOrganizational Climate showed to have a significant influence, either partially ordominantly, on Organizational Citizenship Behaviors. However, the Job Satisfaction showedto have no significant influence on Organizational Citizenship Behavior.Keywords: Organizational Climate, Job Satisfaction, Organizational CitizenshipBehaviors (OCB).